MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI SIFAT-SIFAT BANGUN DATAR MELALUI PENDEKATAN KONTEKSTUAL DALAM PEMBELAJARAN KOOPERATIF TIPE THINK PAIR AND SHARE DI SDN 3 JANGKUNG KABUPATEN TABALONG - Rachmadi Maulana (Universitas Lambung Mangkurat, 2013)
The low of student achievement problem and students less active in mathematics learning process in fifth grade of SDN Jangkung Tanjung Tabalong district due to learning process which isn’t student center yet. The goal of this research was to increase student achievement and activity in mathematics on the subject of Properties of Flat Shape by using contextual approach in Think Pair Share methods. Subject of the study were the fifth grade students consisting of three male and five female students. The observation data was analyzed by using qualitative approach, and the students achievement data was analyzed by percentation. The results showed that student activity score increased from 85.2 and 92.97 in the lesson 1 and 2 in the first cycle to 95.3 and 98.4 in the lesson 1 and 2 in the second cycle. The average score increased from 70 in the first cycle to 81.25 in the second cycle. Classical completeness increased from 62.5% in cycle 1 to 87.5% in cycle 2. From the results of this study can be concluded that the contextual approach in think pair and share model increase learning activity and math achievement on the subject of Properties of Flat Shape of fifth grade students of SDN 3 Jangkung Tabalong district school year 2011/2012. Key words: Learning Outcomes, Properties of Flat Shape, Contextual Approach, Cooperative Learning, Think Pair and Share